PERBANDINGAN HASIL BELAJAR PADA METODE MAKE A MATCH DENGAN WORD SQUARE PADA MATA PELAJARAN GEOGRAFI FASE F SMA NEGERI 1 BATIPUH - Ariyani, Resty; wati, Erna (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The purpose of this study was to determine whether the two learning methods make a match with word Square there is a difference in geography learning outcomes of Phase F XI class students at SMA Negeri 1 Batipuh. The type of research used is quasi-experiment. The population of this study were students of class XI Geography SMA Negeri 1 Batipuh which amounted to 120 students and the sample in this study using simple random sampling technique with a total sample of 56 students divided into experimental groups, namely class XI Geography 2 and control class group XI Geography 1 with each student as many as 28 students. The data analysis technique used is normality test, homogeneity test and hypothesis testing using t-test. The results showed that there was an effect of make a match learning method higher than word square learning method on student learning outcomes. Based on hypothesis testing using the t-test obtained tcount> ttable (2.23> 2.01) on the posttest results of the experimental class and control class. This shows that there is an effect of the make a match learning method higher than the word square learning method in geography class XI Phase F at SMA Negeri 1 Batipuh.